Kajian Sosiologis Novel Merpati Biru Karya Achmad Munif - Ani Diana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the social aspects of the novel Merpati Biru by Achmad Munif. The method is a descriptive qualitative method with a sociological approach. The results showed that the social aspects of the novel Merpati Biru by Achmad Munif consist of social groups, culture, social institutions, social stratification and power and authority. In conclusion, the novel Merpati Biru by Achmad Munif contains many social aspects to serve as material for reflection and lessons for readers that can be used as experiences and references in everyday life. Keywords: Sociological Studies, Merpati Biru Novel